“Do you have questions?” How sequential placement shapes the uptake of question invitations in HPV vaccine treatment recommendations in the Netherlands - Guusje Jol; Tessa van Charldorp; Hedwig te Molder; Nienke van Trommel (SSM: Qualitative Research in Health)
This article concerns public health nurses' invitations to ask questions about HPV-vaccination. The invitations are addressed to children and their parents. Asking questions allows parents and children to gather information they need for an informed decision on whether or not to vaccinate. Our conversation analysis of 36 recorded triadic consultations about general health consultation in the Netherlands identifies two ways in which nurses' questions invitations can be embedded: 1) questions are invited after vaccine treatment recommendation, but before a decision has been made about vaccination - therefore launching an insert expansion, 2) questions are invited after a vaccine treatment recommendation and decision to that recommendation. In the first case, asking questions is treated as raising obstacles to a response to the treatment recommendation. In the second case, a complex interactional environment is set up for asking (critical) questions. The analysis shows that the sequential position of question invitations is important for how these invitations function. It also illustrates that nurses must balance the task of inviting a conversation and securing consent for vaccination.